2021
DOI: 10.1186/s12889-021-12038-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differences in the associated factors of severe under-5 child undernutrition based on the composite index of severe anthropometric failure (CISAF) in Bangladesh

Abstract: Introduction Severe undernutrition among under-5 children is usually assessed using single or conventional indicators (i.e., severe stunting, severe wasting, and/or severe underweight). But these conventional indicators partly overlap, thus not providing a comprehensive estimate of the proportion of malnourished children in the population. Incorporating all these conventional nutritional indicators, the Composite Index of Severe Anthropometric Failure (CSIAF) provides six different undernutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…The overall prevalence of severe undernutrition measured by CISAF among children under 5 was 13.9%. This finding aligns with a study from Bangladesh, which reported a prevalence of CISAF among children under five was 11.0% [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall prevalence of severe undernutrition measured by CISAF among children under 5 was 13.9%. This finding aligns with a study from Bangladesh, which reported a prevalence of CISAF among children under five was 11.0% [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…In Asia, CISAF has been successfully used to demonstrate the prevalence of severe undernutrition among the children under-five. For example in Bangladesh CISAF was 11.0% (rural 11.5% vs. urban 9.6%) [ 31 ], indicative of severe undernutrition in this nation, especially in children residing in rural settings.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Similar to our study, geographical variation and urban-rural variation were noticed in earlier studies. [25] Here children of higher birth orders (4 or more) living in rural areas of Central, eastern, and north-eastern regions of the country are benefitting from Anganwadi centres. Anganwadi centres provide mid-day meals to children throughout the country especially in rural areas via the government-run Integrated Child Development Scheme (ICDS).…”
Section: Discussionmentioning
confidence: 99%
“…Children with low birth weight are more likely to be severely malnourished regardless of geographical context. In a study by Anik et al, (2021) conducted in Bangladesh, it was shown that children with low birth weight were 3.99 times more likely to experience severe undernutrition. In addition, nutrition that is not fulfilled optimally for the mother and fetus during pregnancy will affect the growth and development of the fetus which manifests in the form of low birth weight or LBW (Wong et al, 2020;Kusparina 2019in Prasojo et al, 2022.…”
Section: Bivariate Analysismentioning
confidence: 99%